MICHINE: Sistem Monitoring dan Penyiraman Otomatis untuk Budidaya Microgreen Wheatgrass sebagai Pakan Qurban - Mukhtar, Dimas Ali; Faturrahman, Daffa; Lahwa Alghifari, Muhammad; Joyo Kusumo, Febrian; Maulana, Ade; Kamelia, Lia (Fakultas Teknik Universitas Garut, 2025)
In the modernization era, the livestock sector faces challenges in meeting quality feed demands, particularly during the qurban season. Wheatgrass cultivated via the microgreen method offers a high-nutrient alternative, yet its cultivation requires intensive care, reducing labor efficiency in manual operations. This study aims to design the Microgreen Feed Machine (MICHINE), an automatic watering and monitoring system based on a local web server using ESP-32. A Research and Development (R&D) approach was employed with experimental testing to measure sensor performance and system accuracy. Results indicate that the RTC module successfully scheduled watering with high precision. The DHT22 sensor demonstrated an average temperature accuracy of 99.72% and humidity accuracy of 94.49%, while the ultrasonic sensor effectively detected harvest readiness with minimal error. The implementation of a local web server proved reliable in delivering real-time data without relying on external internet connections. The system significantly enhances operational efficiency by reducing manual intervention, making wheatgrass cultivation for qurban feed more economical and practical.